Non-Spinal Neuromodulation of the Lumbar Medial Branch Nerve for Chronic Axial Low Back Pain: A Narrative Review - Tieppo Francio, Vinicius; Westerhaus, Benjamin D.; Rupp, Adam; Sayed, Dawood (Frontiers in Pain Research, 2022)
Chronic low back pain remains highly prevalent, costly, and the leading cause of disability worldwide. Symptoms are complex and treatment involves an interdisciplinary approach. Due to diverse anatomical etiologies, treatment outcomes with interventional options are highly variable. A novel approach to treating chronic axial low back pain entails the use of peripheral nerve stimulation to the lumbar medial branch nerve, and this review examines the clinical data of the two different, commercially available, non-spinal neuromodulation systems. This review provides the clinician a succinct narrative that presents up-to-date data objectively. Our review found ten clinical studies, including one report of two cases, six prospective studies, and three randomized clinical trials published to date. Currently, there are different proposed mechanisms of action to address chronic axial low back pain with different implantation techniques. Evidence suggests that peripheral nerve stimulation of the lumbar medial branch nerve may be effective in improving pain and function in patients with chronic axial low back pain symptoms at short and long term follow up, with good safety profiles. Further long-term data is needed to consider this intervention earlier in the pain treatment algorithm, but initial data are promising.